How Hospitality and Tourism Students Choose Careers: Influences of Employer Branding and Applicants' Customer Orientation. Issue 4 (2nd October 2018) - Lin, Ming-Yu; Chiang, Chun-Fang; Wu, Kuo-Ping
ABSTRACT: The concept of fit has become an important recruitment issue in recent years. The hotel industry is labor intensive, requiring a large workforce to serve customers, and the demand for staff remains urgent. In this sense, hotels must attract suitable staff to provide excellent customer-oriented service. Therefore, recruitment activities should carefully consider how to deliver messages and further attract appropriate applicants. This study examined whether employer branding and applicants' customer orientation influence applicants' person–job fit and job choice intention. The study found that person–job fit has a mediating effect. The research results suggest that hotels should develop employer branding and seek customer-oriented job applicants to increase the likelihood of hiring excellent employees who can fit within their organizational culture.